Game Potential of Idioms (on Material of Book by Yu. Buyda “Prussian Bride”) - K. A. Degtyarenko; E. V. Kuritskaya (Научный диалог)
A method of semantic transformation of phraseological units is considered, which was presented in the book by Yu. Buyda as literalism. Game technique of literalism is restoring the original, direct meaning of the lexemes constituting a phraseological unit. This is achieved by introducing in the context of the story the literal deploying, pointing to the reality. It is revealed that the polysemy arising from the clash within the context of two meanings of a single phrase (literal and idiomatic) is a source of word play, and often provokes the creation of comic effect. As a literal deploying Yu. Buyda uses the word or phrase linked with a phraseological unit thematically, associatively and by synonymic or antonymic relations. In the writer’s works considered technique illustrates not only the method of updating the semantics of phraseological units, but also has a projective text function. On its basis, the author builds the storyline in many stories that the game intertwined, which creates certain difficulties in identifying both the technique and its gaming potential. It is shown that in most cases, to restore the logical link between the idiom and literal deploying the activation of background knowledge and committing a number of mental operations is required. The analysis is based on the following parameters of literal deploying input: its explicitness / implication, the remoteness of literal deploying from the idiom, the sequence of its input (in a preposition or postposition) and the way of representation of literal deploying.